Assessing the impact of dietary polystyrene nanoplastics on growth performance, immunological parameters, and antioxidant defense in zebrafish (Danio rerio) - Ehsan Ahmadifar; Poulin Shohreh; Naser Kalhor; Mohsen Shahriari Moghadam; Sevdan Yilmaz; Sedigheh Mohammadzadeh; Mostafa Khajeh; Safoura Abarghouei (Journal of the World Aquaculture Society, 2024)
Abstract This trial was performed in order to investigate the response of zebrafish (Danio rerio) to dietary exposure to polystyrene nanoplastics (PS‐NPs) under laboratory conditions on fish growth and health. Healthy zebrafish (n=240) were divided into 12 tanks and fed with diets including 0 (T0), 100 (T1), 500 (T2), and 1000 (T3) mg kg−1 synthesized polystyrenes nanoplastics (PS‐NPs) for 30 days. At the end of trial, fish fed the PS‐NPs supplementation showed weight gain percentages of 79.45%, 70.35%, and 61.88% for T1, T2, and T3 groups, respectively, compared with 87.39% in the control fish. The SOD, GPX and MDA activities and cortisol levels increased by 47%, 32% and 35% and 46%, respectively, especially at high‐dose administration (p < 0.05). The expression of GPX (T2‐81% and T3‐82%) and SOD (T2‐101% and T3‐187%) were remarkably upregulated in T2 and T3 groups. Moreover, the relative gene expression of HSP70, interleukin‐1 (IL1), Interferon γ (IFN‐γ) and tumor necrosis factor‐α (TNF‐α) increased by 178%, 202%, 154% and 307%, respectively, especially at high‐dose administration (p < 0.05). The results of the present study demonstrated that exposure to PS‐NPs especially at high concentrations (500 and 1000 mg kg−1 of diet) negatively influenced growth, health status‐, antioxidant‐, and immunity‐related gene expression responses of zebrafish.